2018
DOI: 10.1111/1751-2980.12565
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors are associated with vitamin D levels in IBD patients: A retrospective analysis

Abstract: Vitamin D deficiency is common in patients with IBD. However, certain clinical situations lead to significantly lower vitamin D levels and may therefore require close monitoring for vitamin D deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 41 publications
5
37
0
Order By: Relevance
“…The same study demonstrated that IBD patients also had increased odds of lower vitamin D levels compared to matched controls. Due to the potential mechanistic link between vitamin D and colitis and the high prevalence of vitamin D deficiency in IBD patients, many groups have sought to examine the impact of vitamin D levels on IBD clinical outcomes, often with conflicting results. Many of these previous studies were limited by their small sample size and inability to detect differences in clinical outcomes between low and high vitamin D groups.…”
Section: Introductionmentioning
confidence: 99%
“…The same study demonstrated that IBD patients also had increased odds of lower vitamin D levels compared to matched controls. Due to the potential mechanistic link between vitamin D and colitis and the high prevalence of vitamin D deficiency in IBD patients, many groups have sought to examine the impact of vitamin D levels on IBD clinical outcomes, often with conflicting results. Many of these previous studies were limited by their small sample size and inability to detect differences in clinical outcomes between low and high vitamin D groups.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models with colitis have been shown to have altered microbiota [45], and vitamin D administration in the same models was shown to alter the gut microbiome and protect against colitis [46]. Similar data exists for CD, where lower vitamin D levels are found in patients with small bowel CD or in those with resected segments of the small bowel [5]. There are some limitations to this study.…”
Section: Discussionmentioning
confidence: 71%
“…An explanation for this might be the fact that the mean SCCAI in the cohort of UC patients studied was overall low and only very few patients had evidence of active disease. There is evidence from various studies that vitamin D levels are lower in patients with active disease [5,9,22,23]. One study demonstrates that patients with UC with low baseline vitamin D levels were also more likely to suffer from disease relapse over months [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations